Molecular cloning and tissue expression analysis of glutamate dehydrogenase gene from Macrobrachium rosenbergii under MrTV infection stress - ZHENG Qunyan; PAN Xiaoyi; SHEN Jinyu; CHEN Shaobo; XU Yang; XU Ting (浙江大学学报. 农业与生命科学版)
Macrobrachium rosenbergii is one of the major aquaculture shrimp, whose larva is the susceptible host of Macrobrachium rosenbergii Taihu virus (MrTV) which is one kind of novel RNA virus, and a member of Dicistroviridae owning a single positive strand with two open reading frames. Glutamate dehydrogenase (GDH) is a key enzyme in glutamate biosynthesis and plays an important role in organism’s metabolism. But there are still few reports about glutamate dehydrogenase in crustaceans, and almost no reports of M. rosenbergii glutamate dehydrogenase (MrGDH), as well as the interaction between MrGDH and MrTV.In this study, the complete sequence of MrGDH gene was cloned by rapid amplification of cDNA ends (RACE) technology, and the expression of MrGDH gene in different tissues was studied by quantitative real-time polymerase chain reaction (qRT-PCR). Then the transcriptional characteristics of MrGDH gene in the gill and hepatopancreas of M. rosenbergii were analyzed under MrTV infection (positive group), and the negative group was injected with phosphate buffered solution.The results showed that the complete cDNA sequence of MrGDH gene was 2 257 bp in length with a 1 662 bp open reading frame (ORF) encoding 553 amino acids, which shared 92% homology with Fenneropenaeus chinensis GDH and Litopenaeus vannamei GDH. The protein molecular mass of MrGDH was approximately 61.37 kDa. Its secondary and three-dimensional structures were extremely similar to Drosophila melanogaster GDH and Bombyx mori GDH. The MrGDH gene was expressed in all detected tissues of M. rosenbergii. After 48 h and 72 h of injection, the expression of MrGDH gene in hepatopancreas and gill of positive group was significantly higher than the negative group.In summary, the MrGDH gene is conservative, and its expression distribution indicates that it’s highly expressed in the organisms extremely related to movement and metabolism, with the highest in muscle and the lowest in haemolymph. This difference may be caused by the diversity in energy demand of each organization. Overall, it is indicated that MrTV infection could stimulate the expression of MrGDH gene.